A depleted workforce. (2nd August 2022) - Oldman, Crystal
Abstract : The decline of the nursing and health visiting workforce in the community appears to be in conflict with the aims and objectives of the NHS Long Term Plan, says Crystal Oldman. Where is the workforce plan to address the problem?